2015
DOI: 10.1055/s-0034-1380677
|View full text |Cite
|
Sign up to set email alerts
|

A Novel One-Pot Method for Highly Regioselective Synthesis of Triazoloapyrimidinedicarboxylates Using Silica Sodium Carbonate

Abstract: A novel synthesis of dimethyl 4,5-dihydro-5-aryl-[1,2,4]triazolo[1,5-a]pyrimidine-6,7-dicarboxylates is reported. This methodology consists of the one-pot condensation of 3-amino-1H-1,2,4-triazole, dimethyl acetylenedicarboxylate, and aryl aldehydes using silica sodium carbonate as a solid base catalyst. The use of silica sodium carbonate as a heterogeneous reusable catalyst makes this procedure mild, convenient, and environmentally benign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…By investigating the aforesaid evidence, the conversion of product 8 to 8' might be occurred by unusual hydride transfer and release of molecular hydrogen (H 2 ) in the presence of [(VO)TPP][(TCM) 4 ]. The C–H bond is weakened via anomeric supporting of the nitrogen lone pairs into the vacant anti-bonding of C–H ( * C–H orbital) 1 , 2 , 91 , 92 which can be reacted with a proton to furnish molecular hydrogen.
Figure 8 Suggested reaction mechanism for the synthesis of 5-amino-7-(aryl)-4,7-dihydro-[1,2,4]triazolo[1,5- a ]pyrimidine-6-carbonitriles 8 and 5-amino-7-(aryl)-[1,2,4]triazolo[1,5- a ]pyrimidine-6-carbonitriles 8' .
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By investigating the aforesaid evidence, the conversion of product 8 to 8' might be occurred by unusual hydride transfer and release of molecular hydrogen (H 2 ) in the presence of [(VO)TPP][(TCM) 4 ]. The C–H bond is weakened via anomeric supporting of the nitrogen lone pairs into the vacant anti-bonding of C–H ( * C–H orbital) 1 , 2 , 91 , 92 which can be reacted with a proton to furnish molecular hydrogen.
Figure 8 Suggested reaction mechanism for the synthesis of 5-amino-7-(aryl)-4,7-dihydro-[1,2,4]triazolo[1,5- a ]pyrimidine-6-carbonitriles 8 and 5-amino-7-(aryl)-[1,2,4]triazolo[1,5- a ]pyrimidine-6-carbonitriles 8' .
…”
Section: Resultsmentioning
confidence: 99%
“…Triazolopyrimidines are among the great substantial hybrid heterocycles of pyrimidine as they are structural fundamentals of bioactive natural target molecules 1 , 2 . These compounds have engrossed much consideration from agricultural and medicinal scientists because of their varied range of biological activities, such as bromodomain inhibitors 3 , leishmanicidal 4 , receptor antagonists 5 , 6 , herbicidal 7 , 8 , antimalarial 9 , 10 , cardiovascular vasodilators 11 , anti-inflammatory 12 , and fungicidal 13 factors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the novel synthesis of dimethyl 4,5-dihydro-5aryl- [1,2,4]triazolo[1,5-a]pyrimidine-6,7-dicarboxylates 324 was reported by B. Karami and coworkers through the one-pot condensation of 3-amino-1H-1,2,4-triazole 25, dimethyl acetylenedicarboxylate 323, and aryl aldehydes 4 using silica sodium carbonate as a solid base catalyst (Scheme 101). 198 2.1.1.9 MCRs involving miscellaneous compounds. Li's group discovered DABCO as a promoter for the reaction between 4-nitrobenzaldehyde 68 and methyl acrylate 325 and subsequent addition of 2-aminobenzimidazole 3a.…”
Section: Aminoazaheterocycles As Binucleophilesmentioning
confidence: 99%
“…Furthermore, the novel synthesis of dimethyl 4,5-dihydro-5-aryl-[1,2,4]triazolo[1,5- a ]pyrimidine-6,7-dicarboxylates 324 was reported by B. Karami and coworkers through the one-pot condensation of 3-amino-1 H -1,2,4-triazole 25, dimethyl acetylenedicarboxylate 323, and aryl aldehydes 4 using silica sodium carbonate as a solid base catalyst ( Scheme 101 ). 198 …”
Section: Classificationmentioning
confidence: 99%
“…Application of heterogeneous solid base, silica sodium carbonate (SSC) as a catalyst allowed isolation of dimethyl 4,5-dihydrotriazolopyrimidine-6,7-dicarboxylates 196 in the MCR of dimethyl acetylenedicarboxylate ( 195 ) with 1 and 5a . The authors (Karami et al, 2015b ) suggested that the base favors the formation of an intermediate product of condensation between nucleophilic NH in the position 2 of 3-amino-1,2,4-triazole ( 5a ) and electrophilic CH-center of dimethyl acetylenedicarboxylate ( 195 ) followed by the attack of aldehyde 1 , cyclization and dehydration (Figure 15 ).…”
Section: Main Partmentioning
confidence: 99%